Institutional deterioration and entrepreneurial investment: The role of political connections - Ge, Jianhua; Stanley, Laura J.; Eddleston, Kimberly; Kellermanns, Franz W. (Journal of Business Venturing, 2017)
Although many start-ups struggle to grow partly due to institutional voids in transitioning economies, empirical observations have contradicted this dominant view in the literature in that even with deficient formal institutions many economies (e.g., China) have high rates of entrepreneurship in recent years. To understand this paradox, we propose a politically contingent view of the relationship between the institutional environment and entrepreneurs' reinvestment in their business. Our empirical study of entrepreneurs in China shows that the impact of institutional deterioration on entrepreneurial reinvestment substantially hinges on entrepreneurs' political connections. As such, institutional deterioration does not reduce entrepreneurial reinvestment for all entrepreneurs; rather, when entrepreneurs have political connections they are willing to reinvest in their business despite a weakening institutional environment. Our framework suggests that in an environment perceived as harsh to business, political connections can encourage entrepreneurs to see opportunities for growth. In contrast, entrepreneurs that lack political connections will mainly see threats in a deteriorating institutional environment and thus, limit their business reinvestment.